APPLICATION OF NEURAL NETWORKS IN CRYPTANALYSIS: MODERN APPROACHES AND PROSPECTS - BURTSO, ANDRII; MARIKUTSA, ULIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In today’s world, the proliferation of digital technologies has revolutionized numerous aspects of modern life, fundamentally reshaping how individuals, organizations, and societies interact and function. However, alongside the numerous benefits brought by this digital transformation, a growing threat has emerged—cybersecurity breaches. As the digital landscape expands and evolves, so do the tactics and capabilities of malicious actors seeking to exploit vulnerabilities for criminal purposes. Consequently, protecting digital assets and infrastructure from cyber threats has become a necessity for individuals, businesses, and governments alike. Addressing the multifaceted challenges posed by cyber threats requires innovative and adaptive approaches that can keep pace with the dynamic nature of digital risks. In this context, artificial intelligence (AI) has emerged as a pivotal technology, offering unprecedented capabilities to enhance cybersecurity defenses. AI encompasses a range of advanced methods and algorithms enabling machines to simulate human intelligence, including learning from data, making predictions, and adapting to new information. The application of AI in cybersecurity holds the promise of significantly improving threat detection, strengthening defenses, and mitigating risks in the digital domain. This article aims to explore the critical role of AI in cybersecurity by examining its applications across various areas, such as threat detection, vulnerability assessment, incident response, and predictive analysis. Leveraging machine learning algorithms and advanced data analytics, AI-driven solutions can analyze vast amounts of data in real time, identifying anomalous patterns indicative of potential security breaches. Furthermore, AI enables organizations to implement proactive defense mechanisms, allowing them to anticipate and mitigate emerging threats before they fully manifest. However, integrating AI into cybersecurity frameworks is not without challenges and complexities. Ethical considerations, privacy concerns, and potential algorithmic biases require a nuanced approach to implementing AI-driven cybersecurity solutions. Thus, this article seeks to critically evaluate the advantages, limitations, and ethical implications of AI in cybersecurity, emphasizing the need to balance innovation with ethical responsibility. At its core, the rise of AI represents a paradigm shift in cybersecurity, offering unprecedented opportunities to strengthen defenses and combat cyber threats in the digital age. Through a comprehensive analysis of AI’s role in cybersecurity, this article seeks to elucidate the transformative potential of AI-based technologies in safeguarding digital assets and preserving the integrity of cyberspace.